Volume 1: Compressors, Fans and Pumps; Turbines; Heat Transfer; Combustion, Fuels and Emissions 2017
DOI: 10.1115/gtindia2017-4816
|View full text |Cite
|
Sign up to set email alerts
|

Oil Flow Simulations in the Lubrication System of a Turbocharger

Abstract: Oil sealing in a turbocharger is a key design challenge. Under certain engine operating conditions oil in the lubrication system is likely to enter the compressor or turbine wheel crossing the piston rings which are used to arrest the undesirable oil flow. Compressor side oil leakage can cause white smoke and particulate emissions. Limited experimental and analytical methods are available to aid the designers in developing the oil flow path. The oil flow path has dimensions of the order of a few microns in cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some effective methods for bearing oil mist leakage proof have been explored in engineering practice for nearly a century. The advances in numerical simulation technology in the past three decades have been crucial in studying the effects and mechanism of this phenomenon [31,32], resulting in bearing designs of excellent performance [33][34][35]. To back up their claims, some scholars have combined numerical methods with experiments [36,37], but the drawbacks include the high cost of the equipment and labor-intensive analysis.…”
Section: Chinamentioning
confidence: 99%
“…Some effective methods for bearing oil mist leakage proof have been explored in engineering practice for nearly a century. The advances in numerical simulation technology in the past three decades have been crucial in studying the effects and mechanism of this phenomenon [31,32], resulting in bearing designs of excellent performance [33][34][35]. To back up their claims, some scholars have combined numerical methods with experiments [36,37], but the drawbacks include the high cost of the equipment and labor-intensive analysis.…”
Section: Chinamentioning
confidence: 99%
“…They designed a novel labyrinth sealing structure based on the simulation analysis of the flow characteristics of leakage flow inside turbocharger, which reduced the leakage flow by 19%. Moreover, the flow path, the flow characteristics and the pressure distribution of leakage flow in sealing structure were deeply studied by Ramachandran et al relying on the constructed oil phase and oil and air two-phase turbocharger models [17]. The mutual authentication of simulation and experiment demonstrated that the simulation approach was able to predict the leakage flow within engineering accuracy and guided the design of low-leakage turbocharger.…”
Section: Introductionmentioning
confidence: 99%